The mammoth book of roaring twenties whodunnits - Ashley, Michael (Carroll & Graf Publishers, 2004)
Mike Ashley's brilliant new collection of whodunnits presents stories that reflect all the excitement, escapism and eccentricity of the 1920s.The Roaring Twenties, the Jazz Age, the Age of Wonderful Nonsense - this was a decade when everyone went a little bit crazy.It was also a decade that saw wonderful detective fiction from the likes of Agatha Christie, Margery Allingham and others. Contributions range from Cornell Woolrich's story of murder at a jazz party set aboard a steamboat on the Mississippi, to Grenville Robbins' impossible homicide committed on the radio, live on air, and Mat Coward's tale of death at a house party hosting the inaugural meeting of the British Communist Party.